Million dollar speaking : the professional's guide to building your platform - Weiss, Alan, 1946- (McGraw Hill-Ascent Audio, 2021)
Make your move into, or improve your position in, the powerful world of professional speaking If you think you have what it takes to speak professionally, or you've already been doing so with insufficient reward, now is the time to make your move. Bestselling business author and Professional Speaking Hall of Fame member Alan Weiss offers the inside advice you need to turn your talent into a high-paying career-from honing your delivery skills to building a business. In Million Dollar Speaking, you'll learn the critical skills of Dealing with difficult crowds Creating powerful speeches Targeting high-potential markets Creating a "star" reputation Setting fees that reflect your outstanding value Perfecting platform skills-making them the best in the business Expanding your business through diversification Weiss has packed the guide with tips, resources, helpful examples, and checklists that make it easy for you to keep a record of your progress. Whether you're a trainer, workshop leader, or consultant, Million Dollar Speaking has what you need to get on the paid public-speaking circuit in no time